Stabilizing the EU electricity market: Mandatory demand reduction and a lower price cap - Reyer Gerlagh; Matti Liski; Iivo Vehviläinen (EconPol Forum, 2022)
A coordinated roll-out of energy-demand reduction would create large external benefits in Europe. Lowering the price cap to exteuro1,000 /MWh in the harmonized EU electricity market would save on costs for users, would not harm supply, and would substantially reduce the need for redistribution policies. European electricity market operators should prepare for the coming winter by adopting well-defined protocols for not only managing electricity shortage situations by rationing, but also for managing extreme spot price levels by rationing. This calls for dynamic price level targets that depend on how demand responsiveness develops during the crises.
Keywords: 330